Decreasing Prolonged Waiting Times for Chemotherapy Administration for Patients with Cancer - Mervat Mahrous; Emad El Shaer; Lamia Rezik; Samar Taha; Ahmed Yosef (Global Journal on Quality and Safety in Healthcare, 2018)
Background: On the basis of our patient satisfaction survey, we initiated a quality improvement project at our institution to decrease waiting times for patients scheduled for chemotherapy. The mean waiting time until a patient started his or her session was 183.5 min. Our aim was to reduce the waiting time by 50% (<90 min) over a 6-month period and to sustain it. Materials and Methods: We used a multidisciplinary approach to identify the root causes and contributing factors of prolonged waiting times for patients in the chemotherapy unit. We implemented three Plan–Do–Study–Act cycles over a 10-month period (February to December 2016). First, we redesigned the nursing triage process, treatment process, and nursing awareness programs. Second, we improved nursing documentation to ensure accurate tracking of patients who declined their appointment or were overbooked. Third, pharmacy forms and chemotherapy preparation were accomplished with the help of an electronic system. We implemented a department-wide standard of care to provide an early assessment of the patient on arrival, and we activated a specific chemotherapy clinic for patient booking and laboratory tests, which were supervised by a trained qualified oncologist. Results: Median time to chemotherapy administration was reduced by 40% in the first 3 months, 64% in 6 months, and 51% in 18 months. We checked every 2 weeks for sustained action and tracked the time from when the patient checked in until he or she received treatment, guided by electronic pharmacy confirmation. The mean waiting time continued to improve and no complaints were reported during the last 6 months of the post-intervention period. Conclusion: Our project resulted in a 40%–64% reduction in waiting times for patients in the chemotherapy unit over an 18-month period. Our plan is to sustain this improvement by continually monitoring waiting times and addressing any emerging issues.